PENGARUH PARTISIPASI ANGGARAN DAN BUDGET EMPHASIS TERHADAP SENJANGAN (SLACK) ANGGARAN DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MODERASI (Studi Kasus Pada PD BPR BKK Kota Semarang) - Ratih Dewi Dewantari, I6.05.62.0004; Jaeni, Jaeni (Students' Journal of Accounting and Banking, 2018)
This research aims to analyze the effect of budget participation and budget emphasis on budgetary slack and whether there is the ability of the organization's commitment to moderate in PD BPR BKK Semarang. This research was conducted on those who participated directly in the preparation of the budget in accordance with the criteria that have been determined by the number of respondents as many as 32 people in PD BPR BKK Semarang. The sampling method used in this study was purposive sampling. The results of this study show that budget participation and budget emphasis berpengruh significant positive toward budgetary slack, organizational commitment able to moderate the effect of budget participation Budget Emphasis on budgetary slack Keywords : budget participation, budget emphasis, organizational commitment, budgetary slack.